2009
DOI: 10.3349/ymj.2009.50.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Dental Findings in Cornelia De Lange Syndrome

Abstract: Cornelia de Lange syndrome is a congenital disease, basically characterized by psychomotor retardation associated with a series of malformations, including mainly skeletal, craniofacial deformities together with gastrointestinal and cardiac malformations. There is no definitive biochemical or chromosomal marker for the prenatal diagnosis of this syndrome. We actually want to present the case of a 10-year-old patient, who was admitted to our clinic for dental pain. The patient had the symptoms of Cornelia de La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
0
14
0
7
Order By: Relevance
“…Finally, in 2009, Toker et al [16] presented a case of a 10 year-old male that was experiencing dental pain, and whose mother reported having a history of preterm births. The patient had the affected teeth extracted under general anesthesia and there were no complications during the process or in the postoperative period.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, in 2009, Toker et al [16] presented a case of a 10 year-old male that was experiencing dental pain, and whose mother reported having a history of preterm births. The patient had the affected teeth extracted under general anesthesia and there were no complications during the process or in the postoperative period.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies published to date regarding CdLS, we found 5 articles that included a single case report [12][13][14][15][16] and an article that included a sample of two patients [11]. (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations